Plant hygiene management for safe vegetable cultivation - International Water Management Institute (International Water Management Institute, 2025)
This video is produced by the International Water Management Institute (IWMI) in partnership with the Department of Agriculture, Sri Lanka (DoA), and the World Vegetable Center under the CGIAR Science Program on “Better Diets and Nutrition” (BDN). The video educates farmers on the importance of maintaining good hygienic practices in vegetable cultivation and guides them on some key hygienic practices for safe production. We would like to thank all funders who support this research through their contributions to the CGIAR Trust Fund.